Intraosseous access as a modern method of fast ensuring the access to the cardiovascular system in conditions of emergency medicine - Czyż, Rafał; Zawłodzki, Mateusz; Czyż, Izabela (Journal of Education, Health and Sport, 2017)
Providing of intravenous access to the injured person is one of the most necessary medical activities executed by medical staff in emergency situation. Many times traditional method of intravenous access is impossible or it could disadvantageously extend time to drug injecting. In such a situations very helpful could be use of available ready to use sets of intraosseous devices. Purpose of this work is to sum up the actual knowledge about intraosseous access, actual recommendations of world organizations and to present indications, contraindications and possible complications in using of intraosseous access. Numerous research studies show that intraosseous devices are safe and easy to use and achieved results of the effectiveness comparable with the central line. Researchers proved that applying intraosseous devices was connected with earlier injecting of the pharmaceutical drugs to the patient. Current literature shows us that intraosseous access is perfect alternative method to traditional intravenous access.